Science, technology and society from the perspective of chemistry teachers at a state public school (Revista Contexto & Educação, 2025)
This article aimed to investigate the understanding of the theme Science-Technology-Society (STS) on the part of Chemistry teachers, linked to the education department of the state of Ceará (SEDUC), and assigned to the Military Police College of this state. To this end, an adaptation of the Cuestionario de Opiniones sobre Ciencia, Tecnología y Sociedad (COCTS) was applied, with assertions scored using an ordinal scale ranging from 1 to 9 for each statement. The research developed here was of a qualitative nature and was guided by a descriptive, exploratory bias. In this study, teachers' understandings regarding the STS approach and its definitions are exposed and discussed. Regarding the conceptions related to the STS interrelationships, the classification “Adequate, Plausible and Naive” was used. In the corollary, the teachers demonstrated credible views regarding the understanding of STS, but at certain points there are naive ideas on the referred subject, pointing to the need for continuing education regarding the compressions of the STS approach.
Keywords: Science; Technology; Society; Chemistry; Police College